Properties of an Fc gamma-binding protein isolated from human leukemic B cells (The Rockefeller University Press, 1979)
A selectively Fc gamma-binding protein was isolated from purified and radioiodinated cell membranes from two cases of B-type chronic lymphocytic leukemia and one case of B-type prolymphocytic leukemia by binding to IgG aggregates, horseradish peroxidase-anti-peroxidase IgG complexes, and sheep erythrocyte membrane sheets densely coated with IgG. This protein could not be isolated from the cell membranes of an Fc gamma-receptor-negative chronic lymphocytic leukemia of the T type or from membranes of human erythrocytes. The Fc gamma-binding protein was efficiently solubilized by a mixture of Na-EDTA and 2- mercaptoethanol, but not with one of these agents alone, indicating that both divalent cations and disulfide bridges are involved in the linkage of the Fc gamma-binding protein to the cell membrane. In sodium dodecyl sulfate-polyacrylamide gel electrophoresis, the Fc gamma- binding protein revealed an apparent mol wt of 28,000 and in isoelectric focusing it showed an isoelectric point of 5.5. The electrophoretic mobility of the 28,000-dalton protein did not change after reduction and alkylation. It was determined that the NH2-terminal amino acid of the protein was glycine. The isolated protein was unable to agglutinate antibody-coated erythrocytes. These findings suggest that the 28,000-dalton IgG-affined protein was composed to O2-enriched buffer lacking reducing agents, the 28,000-dalton protein aggregated to a 115,000-dalton molecule. The isolated Fc gamma-binding protein proved to be different from C1q or its subunits.